Análise multimodal de estratégias discursivas: debate sobre o “bailout” entre Hillary Clinton e Bernie Sanders - Rocha, Nuno (ElingUP : Revista eletrónica de Linguística dos Estudantes da Universidade do Porto, 2019)
Este trabalho consiste numa análise multimodal das estratégias discursivas de Bernie Sanders e Hillary Clinton num excerto de um debate sobre as benesses dadas pela senadora norte americana aos bancos no pós-crise económica global de 2008. Bernie Sanders e Hillary Clinton evidenciaram uma linguagem corporal diferente, tanto na posição de locutor como na de interlocutor. No entanto, mesmo utilizando estratégias de comunicação verbal e física diferentes, os gestos utilizados enquadram-se no campo dos gestos recorrentemente observados em figuras políticas em estudos feitos por outros autores. Reforça-se assim a ideia de que os gestos em questão são regularmente utilizados por figuras políticas.
Number: 2

«Em caso de dúvida ou persistência dos sintomas, consulte o médico ou farmacêutico» O género textual folheto informativo em Portugal - Rocha, Nuno (Universidade do Porto, 2021)
The main focus of this thesis was to characterize the patient information leaftlets as a text genre in Portugal, compare it with the same text genre in other countries and propose a new form of elaborating these documents in order to rise its comprehensibility levels. Therefore, we proceeded with an analysis of the patient information leaflet as a text genre and its relationship with text linguistics and translation. We also analyzed a corpus of 50 patient information leaflets with focus not only on its content, but also in the way they were created. In order to know the opinion of the general public, a survey about the situation of these documents in Portugal was distributed. In order to find the differences between these documents in different contexts, we made a comparison of a portuguese leaflet with leaflets from other countries. By last, we proposed a new writing scheme for these documents, reformulating one of the leaflets analyzed in the corpus and, to get the opinion of the general public, distributing a survey where the reformulated version was compared to the original one. The results point out to a lack of uniformity between documents and the way that they are created in pharmaceutical companies. The content of the patient informations leaflets in Portugal has an excess of text, technical language and a visual organization that is not appealing, problems that were also pointed out by the public in a survey. In the comparison between leaflets of different countries, big differences were found even when they were produced by the same company. When confronted with the original version and the reformulated version of the same document, the general public prefered the latter.
Accepted: 2022-09-09T20:44:50Z